Gold and Silver - but safe? - Parak, N.; Lippusch, M.; Naylor, C.; Steyskall, A.; Joubert, Isabella A.; Himly, Martin; Geppert, Mark (Open Schools Journal for Open Science, 2020)
Gold (Au) and silver (Ag) nanopartucles (NPs) are frequently used in medicine (drug delivery, wound dressings) but also more and more icorporated in every-day life products, such as functional clothing. Therfore, a comprehensive dafety assessment of such particles is essential. Teh aim of this work was the investigation of the suitability of standard DIN-EN-ISO protocolis for cytotoxicity assessment of NPs.